2009
DOI: 10.1016/j.jtcvs.2009.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Lobectomy by video-assisted thoracic surgery (VATS) versus thoracotomy for lung cancer

Abstract: VATS lobectomy and thoracotomy demonstrated similar 5-year survivals. However, VATS lobectomy was associated with fewer complications and shorter length of hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
232
3
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(267 citation statements)
references
References 16 publications
19
232
3
8
Order By: Relevance
“…This outcome could be attributed to the lesser invasion of VATS surgery, a result that is also consistent with reported studies. 26,30,31,34,35 …”
Section: Discussionmentioning
confidence: 99%
“…This outcome could be attributed to the lesser invasion of VATS surgery, a result that is also consistent with reported studies. 26,30,31,34,35 …”
Section: Discussionmentioning
confidence: 99%
“…The long-term impact of postoperative pulmonary complications after video-assisted thoracic surgery lobectomy for lung cancer advantages, quicker postoperative recovery, less postoperative complications, especially for the elderly patients with low pulmonary function or comorbidities (12)(13)(14)(15)(16), PCs are still inevitable, therefore, accurate prediction of PCs is of great clinical significance, which can improve the quality of life and long-term survival of lung cancer patients. However, most of the studies concerned about the presence of PCs, without the severity of the complications.…”
Section: Original Articlementioning
confidence: 99%
“…For patients requiring a lobectomy, studies have demonstrated equivalence in morbidity, mortality, and oncologic outcome at 5 years (5)(6)(7)(8). Some areas such as length of stay and cost may even be superior in VATS (7,9).…”
Section: Vatsmentioning
confidence: 99%